Early viral uptake and host-associated immune response in the tissues of seven-band grouper following a bath challenge with nervous necrosis virus. Issue 103 (August 2020) - Krishnan, Rahul; Kim, Jong-Oh; Qadiri, Syed Shariq Nazir; Kim, Jae-Ok; Oh, Myung-Joo
Abstract: In the present study, early uptake of nervous necrosis virus (NNV) in the tissues (gill, brain, skin, eye, heart) and immune response associated with the uptake in the gill and brain of seven-band grouper was investigated. The gill was found to act as a primary portal of entry for NNV during the initial phase of the water-borne infection. The presence of viral genome and infectious particles was demonstrated using quantitative (qPCR, viral titer) and qualitative (ISH) approach. Initially, an increased viral uptake was noticed, but the virus got cleared from the gills at the later phase of infection. Localization in the brain was evident at the blood-brain barrier followed by the brain parenchyma in the latter stage of infection. Nectin-4, an established NNV receptor, and GHSC70 showed an up-regulated expression throughout the challenge period initially in the gill and at latter phase in brain; however, it seems that the virus does not use gill as a primary replication site but brain as a permissive tissue. Combined activity as reflected by the up-regulation of cytokine, interferon, antigen-presenting cell, and immunoglobulin genes restricts early NNV replication in gill. Observations from the present study provide a better understanding of early NNV entry and also opens a window for further elucidating the modes of NNV neuro-invasion through systemic circulation. Highlights: Gill was found to be the primary portal of NNV entry during water-borne infection. The NNV doesn't use gill as a primary replication site during the early uptake phase. NNV localizes in the Blood brain barrier in the early phase of neural infection. The uptake is characterized by the marked expression of cellular receptors, cytokines and viral PRR.